Fatuma Hussein speaks about Kenya's National Adaptation Planning Process - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Video interview with Fatuma Hussein, acting Director Climate Change Secretariat within the Ministry of Environment, Water and Natural Resources in Kenya